English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

show work please

2006-10-22 10:09:34 · 4 answers · asked by anderson a 1 in Science & Mathematics Mathematics

4 answers

6x = 3x^2 - 1 --> 3x^2 - 6x -1 = 0
Since you can't factor this out, you have to use
the quadratic formula for this. So,
x = -b±√b^2-4ac/2a = 6±√36-4x3x(-1)/2x3 =
6±√48/6

So, the answer will be
6+√48/6 or 6-√48/6
So, it's 1+√48/6 or 1-√48/6.

I'm not sure if this is right. Can somebody check this for me?

2006-10-22 10:28:05 · answer #1 · answered by extra 2 · 0 0

Move everything to one side.
0 = 3x^2 - 6x -1
Use quadratic formula
to get x1 = 2.1547 x2 = -0.1547

2006-10-22 10:25:21 · answer #2 · answered by Crellos 2 · 0 0

simple algebra
find the root using quadratic equ

here is the exact form
x= -(2sqrt(3)-3)/3 or x= (2sqrt(3)+3)/3

Or approximately

x= -.154701 or x = 2.1547

2006-10-22 10:18:32 · answer #3 · answered by Anonymous · 0 0

need to use the quadratic formula, which I don't know off the top of my head.

2006-10-22 10:20:51 · answer #4 · answered by jg 2 · 0 0

fedest.com, questions and answers